2002
DOI: 10.1126/science.1067025
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Guanine Nucleotide Exchange Factor Activates ARF on Legionella Phagosomes

Abstract: The intracellular pathogen Legionella pneumophila subverts vesicle traffic in eukaryotic host cells to create a vacuole that supports replication. The dot/icm genes encode a protein secretion apparatus that L. pneumophila require for biogenesis of this vacuole. Here we show that L. pneumophila produce a protein called RalF that functions as an exchange factor for the ADP ribosylation factor (ARF) family of guanosine triphosphatases (GTPases). The RalF protein is required for the localization of ARF on phagosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
564
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(583 citation statements)
references
References 30 publications
16
564
0
3
Order By: Relevance
“…The genomes of Legionella and of Rickettsia encode a type IV effector with a Sec7 domain homologous to that of eukaryotic ArfGEFs which functions as a GEF to activate host Arf GTPases. 65 The structure of Legionella RalF showed that the Sec7 domain is strongly autoinhibited by a C-terminal domain that blocks access to the Arf-binding site, 66 and a similar autoinhibited conformation was observed in the Rickettsia RalF homolog. 67 Both bacterial ArfGEFs are strongly activated by membranes, and the membrane-binding site is identical to the elements in the autoinhibitory domain that blocks the Arf-binding site.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 89%
See 1 more Smart Citation
“…The genomes of Legionella and of Rickettsia encode a type IV effector with a Sec7 domain homologous to that of eukaryotic ArfGEFs which functions as a GEF to activate host Arf GTPases. 65 The structure of Legionella RalF showed that the Sec7 domain is strongly autoinhibited by a C-terminal domain that blocks access to the Arf-binding site, 66 and a similar autoinhibited conformation was observed in the Rickettsia RalF homolog. 67 Both bacterial ArfGEFs are strongly activated by membranes, and the membrane-binding site is identical to the elements in the autoinhibitory domain that blocks the Arf-binding site.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 89%
“…68,69 Thus, activation of Arf GTPases by RalF strictly depends on its recruitment to membranes. Legionella RalF produces Arf-GTP at the surface of the Legionella-containing vacuole where the pathogen hides and replicates; 65 however Rickettsia replicates in the host cytosol and therefore should use RalF for different functions. In that regard, it is remarkable that Legionella and Rickettsia RalF respond to different membrane characteristics for their activation.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%
“…RalF is translocated through the phagosomal membrane where it recruits and activates ARF1, a member of the ADP RIBOSYLATION FACTOR family of guanosine triphosphatases (GTPases) to the phagosomal membrane. Although the function of ARF1 during infection is not yet defined, RalF recruitment and activation of ARF1 is postulated to enhance the efficiency of replicative vacuole formation 104 . As with the A. tumefaciens and H. pylori T4S systems, there are recent indications from several laboratories that the L. pneumophila Dot/Icm system might translocate additional effectors during its infection cycle.…”
Section: Pneumophila Dot/icm Substratesmentioning
confidence: 99%
“…The icm/dot type IV secretion system is the major virulence system known in L. pneumophila; this system consists of 26 Icm/Dot proteins that probably constitute the secretion complex itself, as well as accessory proteins, such as chaperones (for a review, see reference 49). In the last 5 years, a growing number of protein substrates (RalF, LidA, Lep, Sid, Vip, Wip, Ylf, Leg, Vpd, Drr, and Ceg) that are translocated into host cells via the icm/dot secretion system were identified (for a review, see reference 42); in most cases the function of these proteins is not known, but two of them (SidF and SdhA) were shown to be required for inhibition of host cell death (5,27) and four others (RalF, LidA, DrrA/SidM, and SidJ) were shown to be required for manipulation of host cell vesicular trafficking (28,31,37,38), as well as other functions (11). Even though many icm/dot genes and many more icm/dot translocated substrates (IDTS), as well as potential IDTS, have been identified, there is only a limited amount of information about direct regulators that control the levels of expression of these genes.…”
mentioning
confidence: 99%